2018
DOI: 10.1002/advs.201800781
|View full text |Cite
|
Sign up to set email alerts
|

A Broad‐Spectrum ROS‐Eliminating Material for Prevention of Inflammation and Drug‐Induced Organ Toxicity

Abstract: Despite the great potential of numerous antioxidants for pharmacotherapy of diseases associated with inflammation and oxidative stress, many challenges remain for their clinical translation. Herein, a superoxidase dismutase/catalase‐mimetic material based on Tempol and phenylboronic acid pinacol ester simultaneously conjugated β‐cyclodextrin (abbreviated as TPCD), which is capable of eliminating a broad spectrum of reactive oxygen species (ROS), is reported. TPCD can be easily synthesized by sequentially conju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
124
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 108 publications
(128 citation statements)
references
References 70 publications
3
124
0
Order By: Relevance
“…As shown in Fig. 1f, a characteristic triplet signal of the nitroxyl radical was observed clearly, confirming the presence of TEMPOL radicals in the electrospun membranes [34,35]. Moreover, the loading amount of TEMPOL can be adjusted by simply varying the concentration of TEMPOL solution (i.e., the core layer spinning solution).…”
Section: Resultssupporting
confidence: 63%
“…As shown in Fig. 1f, a characteristic triplet signal of the nitroxyl radical was observed clearly, confirming the presence of TEMPOL radicals in the electrospun membranes [34,35]. Moreover, the loading amount of TEMPOL can be adjusted by simply varying the concentration of TEMPOL solution (i.e., the core layer spinning solution).…”
Section: Resultssupporting
confidence: 63%
“…Compared to ROS‐responsive nanocarriers based on other materials, such as poly(propylene sulfide), selenium‐containing copolymers, polydopamine, and materials bearing polythioether ketal or thioketal linkers, OxbCD‐derived NPs are highly sensitive to H 2 O 2 . More importantly, our comprehensive in vitro and in vivo studies have revealed good safety profile for nanocarriers based on OxbCD . Consequently, we hypothesize that the ROS‐responsive nanocarrier ON can revive orally delivered Ac2‐26 by protecting it from degradation and selective release in the inflamed colon of IBD.…”
Section: Discussionmentioning
confidence: 86%
“…[51] Consistently, we found complete hydrolysis of Ac2-26 after it was incubated in different solutions simulating gastric/intestinal fluids. [30][31][32][33][34]36,54,55] Consequently, we hypothesize that the ROS-responsive nanocarrier ON can revive orally delivered Ac2-26 by protecting it from degradation and selective release in the inflamed colon of IBD. [30,31] Compared to ROS-responsive nanocarriers based on other materials, such as poly(propylene sulfide), selenium-containing copolymers, polydopamine, and materials bearing polythioether ketal or thioketal linkers, [52,53] OxbCD-derived NPs are highly sensitive to H 2 O 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, anti‐inflammatory materials have been investigated as therapeutics against inflammation‐associated diseases. For example, nanoparticles (NPs) capable of eliminating reactive oxygen species (ROS) have demonstrated their efficacy in animal models of peritonitis, rheumatoid arthritis, colitis, nonalcoholic steatohepatitis, acute lung injury, sepsis, atherosclerosis, and ischemic stroke . NPs assembled by PEGylated bilirubin can function as a potent anti‐inflammatory nanotherapy for the treatment of colitis and asthma, by effectively scavenging ROS and modulating the immune system.…”
mentioning
confidence: 99%